Analysis of non-protein amino acids as specific markers of low density lipoprotein apolipoprotein B-100 oxidation in human atherosclerotic lesions: the use of N(O)-ethoxycarbonyl trifluoroethyl ester derivatives and GC-MS 1. Issue 2 (2004) - Pietzsch Pietzsch, Jens Jens; Bergmann Bergmann, Ralf Ralf; Kopprasch Kopprasch, Steffi Steffi
Abstract : Oxidative modification of proteins can interfere with critical cellular functions, and is widely regarded as a crucial event in the pathogenesis of various diseases ranging from rheumatoid arthritis to atherosclerosis and cancer. In this line, a new GC‒MS methodology using N ( O )‒ethoxycarbonyl trifluoroethyl amino acid esters (ECEE‒F3 ) for rapid and sensitive determination of 3‒chlorotyrosine, 5‒hydroxy‒2‒aminovaleric acid (HAVA), and 6‒hydroxy‒2‒aminocaproic acid (HACA) in proteins has been developed. 3‒Chlorotyrosine is a highly specific marker of myeloperoxidase catalyzed protein oxidation, whereas γ‒glutamyl semialdehyde (γGSA) and α‒aminoadipyl semialdehyde (αASA), which by reduction form HAVA and HACA, respectively, are specifically formed by metal catalyzed oxidation processes. ECEE‒F3 derivatives are formed by the unlabored reaction of amino acids with ethylchloroformate plus trifluoroethanol plus pyridine. The key steps of the methodology employed are (i) enzymatic hydrolysis of target proteins to prevent decomposition of oxidation products during hydrolysis and (ii) an uniquely rapid derivatization of amino acids completing sample preparation for GC within a few minutes in aqueous solution at room temperature. The use of these stable products of protein amino acid side chain oxidation as potential markers for assessing oxidative damage in LDL apoB‒100 recovered from human aortic vascular lesions is demonstrated. These observations provide quantitative chemical evidence for metal catalyzed oxidative processes in the human artery wall.